2018
DOI: 10.1021/acs.langmuir.8b01181
|View full text |Cite
|
Sign up to set email alerts
|

Multiform Sulfur Adsorption Centers and Copper-Terminated Active Sites of Nano-CuS for Efficient Elemental Mercury Capture from Coal Combustion Flue Gas

Abstract: Nanostructured copper sulfide synthesized with the assistance of surfactant with nanoscale particle size and high Brunauer-Emmett-Teller surface area was for the first time applied for the capture of elemental mercury (Hg) from coal combustion flue gas. The optimal operation temperature of nano-CuS for Hg adsorption is 75 °C, which indicates that injection of the sorbent between the wet flue gas desulfurization and the wet electrostatic precipitator systems is feasible. This assures that the sorbent is free of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 68 publications
5
106
0
Order By: Relevance
“…These deficiencies in basic understanding of covellite created a huge gap between experimental and theoretical studies. For example, the CuS material shows great potential in the removal of elemental mercury according to extensive studies in recent years, but the removal mechanism is still not well understood yet, especially for its high mercury adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These deficiencies in basic understanding of covellite created a huge gap between experimental and theoretical studies. For example, the CuS material shows great potential in the removal of elemental mercury according to extensive studies in recent years, but the removal mechanism is still not well understood yet, especially for its high mercury adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that polysulfides can stabilize copper-deficit covellite by DFT + U calculations. Li et al deduced that polysulfides on CuS surfaces may contribute greatly in mercury removal according to the XPS analysis . Poly-sulfur ions S x 2– are regarded as the primary sites of CuS x /layered double hydroxide (LDH) composite for Hg 0 oxidation and immobilization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the Hg 0 adsorption capabilities of traditional ACs (< 5 mg g –1 ) are largely suppressed due to limited active sites carried by ACs. Second, the Hg 0 removal efficiency of ACs was also demonstrated to be inhibited by typical industrial flue gas components such as water vapor (H 2 O) and sulfur dioxide (SO 2 ). , Thus, adopting ACs for industrial Hg 0 removal is estimated to be pricey, reaching $14,400/lb of Hg to $38,200/lb of Hg for 99% removal efficiency in a coal combustion scenario . Moreover, the immobilization of Hg 0 on AC surfaces primarily relies on physisorption, which undergoes severe re-emission issues and inevitable secondary pollution when the Hg-laden ACs are dumped and landfilled . From these perspectives, it is of urgent importance to develop novel sorbents that are highly efficient for Hg 0 uptake, insusceptible to typical industrial flue gas components, and capable of permanently sequestrating Hg 0 from polluted sources.…”
Section: Introductionmentioning
confidence: 99%
“…In industries, fixed beds of sulfur-impregnated activated carbons, metal sulfides , as well as silver-impregnated molecular sieves are typically deployed in both regenerative and nonregenerative methods to reduce the mercury concentration of contaminated streams to fewer than 10 ng·m –3 , by means of amalgamation, absorption, chemical, and physical adsorption. However, issues such as the leaching of sulfur and capillary condensation of carbons in wet streams have directed research toward the examination of alternative, highly selective, efficient, reusable, and environmentally friendly sorption materials.…”
Section: Introductionmentioning
confidence: 99%